Laparoscopy in ALPPS procedure: when we can do it? - Barros Schelotto, Pablo (2017)
Totally laparoscopicALPPS procedure performed on a patient withbilateral colorectal liver metastases, and tocontribute to his proposal with a new conceptto accomplish these cases.1 The goal of thisprocedure is to avoid adhesions in the firstsurgery and to facilitate the second-stage hepatectomy.Therefore, a less invasive surgicalprocedure can be offered in these cases, aimingto reduce the number and severity ofpostoperative complications. LaparoscopyALPPS can be planned before surgery for apatient with a small future liver remnant.